Dual inoculation of bacterial on nutrients uptake of in vitro banana plantlets / Zuraida, A.R…[et al.] - A.R, Zuraida; M., Marziah; Z., Shamsuddin; M.S, Halimi (2008)
A experiments were carried out to observe the effects of dual inoculation of rhizobacterial and agrobacterial on nutrients of in vitro banana plantlets using MS basal medium. Dual inoculation of rhizobacteria (Azospirillum brasilense Sp7, Bacillus sphaericus UPMB10 and Microbacterium oxydens UPMB11) and agrobacteria (Agrobacterium rhizogenes strains AR9402 and A4) showed positive response in enhancing nutrients uptake of banana plantlets which, combination of UPMB10 with AR9402 or A4 treatments was the most effective treatment. The combined inoculation has advantages over the single inoculation especially in enhancing nutrients uptake of the plantlets. The results of the study clearly showed that combined inoculation of rhizobacteria and agrobacteria is a promising technique to enhance the nutrient uptake of in vitro banana plantlets.